Board governance mechanisms and liquidity creation: Empirical evidence from GCC banking sector - ALI K.A. Mousa; Nor Laili Hassan; Kashan Pirzada (Cogent Business & Management, 2023)
While various board governance mechanisms, such as board independence, expertise, diversity, and committee structures, play a crucial role in overseeing and guiding bank operations, the extent of their impact on liquidity creation as the preeminent function of the GCC banking sector remains unclear and unexplored. To fill this gap, therefore, this study examines the impact of board governance attributes on liquidity creation in the GCC banking sector. In addition, this study investigates the moderating effect of government ownership on the association between board governance features and bank liquidity creation. To accomplish the objectives of our study, a sample of 68 listed banks over the period of 2010-2021 in the GCC region were employed, and feasible generalized least squares (FGLS) regression was used. The findings indicate that board governance mechanisms in terms of independence, foreign directors, education level, meetings, and board size play a positive role in enhancing bank liquidity creation, whereas the presence of female board members does not affect liquidity creation. Moreover, the supplementary analyses and endogeneity tests provide further validation for the primary regression results, thereby confirming the robustness of the findings. The study's findings are among the earliest empirical evidence of the effect of board governance attributes on liquidity creation in the GCC banking sector.
Keywords: 650; agency theory; board attributes; corporate governance; GCC; liquidity creation